Three dimensional ultrasound of retinoblastoma: initial experience. Issue 10 (1st October 2002) - Finger, P T; Khoobehi, A; Ponce-Contreras, M R; Rocca, D Della; Garcia, J P S
Abstract : Aim: To use 3D ultrasonography (3DUS) for the diagnosis of retinoblastoma. Methods: Five eyes of three children with retinoblastoma were evaluated using a commercially available computerised 3DUS system. Interactive sectioning of the stored and reconstructed 3D volumes were performed. 3DUS and histopathological findings were correlated after enucleation. Results: 3DUS examination revealed characteristics consistent with retinoblastoma: endophytic mass, retinal detachment, intratumoural calcifications, and secondary orbital shadowing. Unlike 2D imaging, 3DUS allowed for analysis of the acquired and stored volumes. Rotation and sectioning of this volume allowed the discovery of new oblique and coronal views. For example, calcium related orbital shadows were seen as 3D volumes and (coronal) cross sections of the optic nerve were evaluated for evidence of intraneural invasion by retinoblastoma. Conclusion: This is the first reported series of patients examined with 3DUS imaging for retinoblastoma. This technique allowed for new oblique and coronal views of the tumour and optic nerve. The ability to retrospectively analyse the (scanned and stored) ocular volume facilitated patient care, teaching, tumour-volume analysis, and telemedicine.